Fatty acid concentration, proximate composition, and mineral composition in fishbone flour of Nile Tilapia Concentración de ácidos grasos, composición centesimal y composición mineral en harina del espinazo de Tilapia del Nilo - Maria Eugênia Petenuci; Flávia Braidoti Stevanato; Jeane Eliete Laguila Visentainer; Makoto Matsushita; Edivaldo Egea Garcia; Nilson Evelázio de Souza; Jesui Vergilio Visentainer (Archivos Latinoamericanos de Nutrición, 2008)
Nile tilapia (Oreochormis niloticus) fishbone is a fish part with unknown composition. After elaboration of flour fishbone of tilapia it was analysede. The results in100g of flour were: moisture (14.2%), protein (40.8%), total lipids (25.3%), and ash (18.3%), and mineral (in 100g) was 2715.9mg (calcium), 1.3mg (iron), and 1132.7mg (phosphorus). A total of 22 fatty acids were detected in fishbone flour total lipids (TL), being the major ones in (g) of total lipids: 16:0 (208.5mg); 18:1n-9 (344.3mg); and 18:2n-6 (109.6mg). The concentration of linolenic acid - LNA (18:3n-3); eicopentaenoicacid - EPA (20:5n-3), and docosahexaenoic acid - DHA (22:6n-3) were (29.9mg), (3.3mg), and (12.9mg), respectively. The content to saturated (SFA) were (296.2mg), monounsaturated (MUFA) 415.0mg, and polyunsaturated (PUFA) 175.6mg. The ratio PUFA:MUFA:SFA was 1:2.4:1.7, and the ratio omega-6/omega-3 fatty acids were 2.8. The last is within the recommended values. The results show low concentrations of omega-3 fatty acids in flour. The value caloric and calcium, iron, phosphorus, and protein content the fishbone flour of tilapia may results a valuable alternative food in the human diet. El espinazo de tilapia (Oreochormis niloticus) es una parte del pescado con composición desconocida. Se obtuvo y analizó la harina de espinazo de tilapia. Los resultados hallados cada 100 gramos de producto fueron: humedad (14,2g), proteina (40,8g), lípidos totales (25,3g), cenizas (18,3g) y calorias (391Kcal). El contenido de minerales en 100g fue calcio (2715,9mg), hierro (1,3mg), y fósforo (1132,7mg). Un total de 22 ácidos grasos fueron encontrados en los lípidos totales de la harina de espinazo, siendo los mayoritarios por g de lípidos totales:16:0 (208,5mg); 18:1n-9 (344,3mg) y 18:2n-6 (109,6mg). La concentración de ácido linolênico - LNA (18:3n-3); ácido eicosapentaenóico - EPA (20:5n- 3), y ácido docosahexaenóico - DHA (22:6n-3) fueron (29.9mg), (3.3mg), y (12.9mg), respectivamente. El contenido de los saturados (SFA) fue 296,2mg, monoinsaturados (MUFA) 415,0 mg y polinsaturados (PUFA) 175,6mg. La razón PUFA:MUFA:SFA fue 1:2,4:1,7 y la razón ácidos grasos omega-6/ácidos grasos omega-3 fue 2,8. Esta última está de acuerdo con los valores recomendados. Los resultados mostraron bajas concentraciones de ácidos grasos omega 3 en la harina; sin embargo, por su aporte calórico, y por su contenido de calcio, hierro, fósforo y proteínas la harina del espinazo de tilapia puede resultar una alternativa interesante para la dieta humana.